Basic measurements of radiation at station Paramaribo (2019-01 et seq) - Ankie Piters (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Paramaribo that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).